Do religiosity, gender and educational background influence zakat compliance? The case of Malaysia - Abdullah, Mazni; Sapiei, Noor Sharoja (Emerald, 2018)
Purpose: The purpose of this paper is to examine the influence of religiosity, gender and Islamic educational background of Muslims on zakat compliance. It also aims to identify which dimensions of religiosity are significantly related to zakat compliance. Design/methodology/approach: The study uses a self-administered questionnaire that was distributed to working Muslims individuals in Klang Valley, Malaysia. Analysis of the data was based on 690 usable questionnaires. Findings: The findings show that religiosity had a significant influence on zakat compliance and three dimensions of religiosity, namely obligation, virtues and vices, and optional ritual, were significantly related to zakat compliance. Gender was also significantly related to zakat compliance, but in a negative direction, suggesting that Muslim working females are less compliant to zakat obligations compared to their male counterparts. It is found that formal Islamic educational background had no significant influence on zakat compliance. Practical implications: Given the importance of zakat collection to the growth of the economy and society, the findings of this paper might provide some insights to Muslim-majority countries and zakat institutions which areas require more attention to encourage zakat payment among Muslims. Originality/value: Compared to prior zakat studies, the findings of this study were derived from a larger sample size of Muslim working respondents. Furthermore, this study also identifies which dimensions of religiosity are significantly related to zakat compliance. Hence this study enriches the scarce literature on zakat and religiosity.